Letter from Linus Pauling to Aaron Klug, October 1, 1959 - Pauling, Linus (1959)
Linus Pauling (1901-1994) writes to Aaron Klug (1926-2018), inviting him to meet in Pasadena, California to discuss his work on viruses with icosahedral symmetry.
Keywords: Klug, A. (Aaron), Sir, 1926-2018; Pauling, Linus, 1901-1994; Viruses